Evaluation of the Development of Student Diversity at State Elementary School Sukasari Cileunyi Bandung - Andewi Suhartini; Agus Hidayat; Ujang Koswara; Pipih Santora; Desi Rosulina; Hamdan Maulana (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of students’ religious character is a fundamental aspect of character education at the elementary school level. This study aims to evaluate the implementation of religious development programs at State Elementary School Sukasari Cileunyi Bandung and to identify the supporting factors, obstacles, and their contributions to shaping students’ religious behavior. Employing a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation involving Islamic education teachers, homeroom teachers, the school principal, and students. The findings reveal that religious development is carried out through worship habituation, teacher role modeling, reinforcement of Islamic education learning, and extracurricular activities. Key supporting factors include the consistency of teachers’ roles, a conducive school environment, and parental involvement, while the obstacles comprise student discipline issues, limited worship facilities, and differences in family religious culture. These findings underscore the importance of habituation and exemplary behavior as core approaches in shaping the religious character of elementary school students. Theoretically, the study enriches the discourse on the effectiveness of habituation-based religious education. Practically, the results provide recommendations for improving religious programs in elementary education institutions so that they may become more systematic and measurable.